Investigation of the Pathology of Brain Derived Endothelial Cells in In-Vitro Hypoxia Models - Erdemli, Kısmet Tuğçe; Erdemli, Kısmet Tuğçe; Tosun, Çiğdem (01. Izmir Institute of Technology, 2021)
The blood brain barrier (BBB) is a vital structure that protects brain homeostasis. Endothelial cells (EC) have a significant role in regulating the BBB structure and function. Several studies have revealed the association of SUR1-TRPM4 channels that regulate this secondary damage of CNS injuries. After the activation of the channel, Na+ influx causes depolarization, cell swelling (edema) and ultimately oncotic cell death. Hypoxia inducing factor (HIF) transcription factor that has been reported to activate more than 100 genes to adapt to a hypoxic condition. Once Hif1-⍺ is translocated into the nucleus, it can dimerize with HIF1-ß to produce HIF that is critical in hypoxic conditions and regulate cell cycle arrest or cell death pathways. Hypoxia can occur in an O2 dependent and independent manner. In this study, CoCl2 and hypoxia chamber which was cost-effective and reliable were optimized. Cellular death was calculated with Trypan blue staining in this novel hypoxia chamber model and compared with CoCl2 models. In addition, morphological changes were observed in microscopic analysis. Hif1-⍺, caspase-3 and NF-κB translocation to the nucleus localization were quantified. Cell viability was different between the CoCl2 model and novel hypoxia chamber model at 24 hours. The cellular death increased with CoCl2 exposure, where no change was noted in the hypoxia chamber model. Time dependent Hif1-⍺ upregulation was also demonstrated that peaked at 12-hours. Finally, NF-κB translocation into the nucleus was significantly increased at 24 hours of hypoxia exposure. The results reveal that the inflatable hypoxia chamber model could be reliably used to mimic hypoxia in an in-vitro setting. Hif1-⍺ activated in a time dependent manner, along with NF-κB. The upregulation of these transcription factors can ultimately affect the cellular death mechanisms differently

Kan-beyin bariyeri (KBB), beyin homeostazını koruyan önemli bir yapıdır. KBB yapısını ve işlevini düzenlemede endotel hücreleri önemli bir role sahiptir. Birçok çalışma, merkezi sinir sistemi (MSS) yaralanmalarının, ikincil hasarı düzenleyen SUR1- TRPM4 kanalları ile ilişkisi olduğunu ortaya çıkarmıştır. Kanalın aktivasyonu ile Na+ hücre içine geçer daha sonra ise, depolarizasyona, hücre şişmesine (ödem) ve onkotik hücre ölümüne sebep olur. Hipoksi indükleyici faktör 1 (HIF1), hücrelerde hipoksik ortama uyum sağlamak için 100'den fazla geni aktive eder. Hif1-⍺ çekirdeğe geçtikten sonra HIF1-ß ile HIF1'ı oluşturur. HIF1 hipoksik koşullara uyum sağlamak ile görevli birçok farlı gen transkripsiyonunu düzenler. Bunlar, hücre döngüsünü düzenleyen genler ya da hücre ölümünü tetikleyen genler olabilir. HIF1 O2 den bağımlı ya da bağımsız şekilde aktive edilebilir. Bu çalışmada, uygun maliyetli ve güvenilir hipoksi modeli ile birlikte CoCl2 modeli optimize edilmiştir. Hücre ölümü, yeni hipoksi modelinde ve CoCl2 modelinde Tripan mavisi boyaması ile hesaplandı Ek olarak, mikroskobik analizde morfolojik değişiklikler gözlemlendi. Çekirdekteki Hif1-⍺, kaspaz-3 ve NF-κB translokasyonu analiz edildi. Hücre ölümü, 24-saat hipoksik ortama maruz kalmış CoCl2 modeli ve yeni hipoksi modelinin sonuçları birbirinden farklıydı. Hipoksi modelinde hücre ölümünde hiçbir değişiklik olmazken, CoCl2 modelinde hücre ölümü artmıştır. Zamana bağlı Hif1-⍺'nin çekirdekteki translokasyonu 12 saatte zirve yaptığı gözlemlenmiştir. Ayrıca, NF-κB'nin çekirdeğe translokasyonu, 24 saatlik hipoksik koşullarda önemli ölçüde arttı. Sonuçlara göre yeni hipoksi modeli, in-vitro ortamda hipoksiyi taklit etmek için kullanılabilmektedir. Hif1-⍺, NF-κB ile birlikte zamana bağlı bir şekilde aktive edildi. Transkripsiyon faktörlerinin artması ya da azalması, hücresel ölüm mekanizmalarını farklı şekilde etkileyebilir.
Beyin Endotel Hücreleri'nin İn-vitro Hipoksi Modelleri ile Karakterizasyonun İncelenmesi
Includes bibliographical references (leaves. 51-62)
Thesis (Master)--Izmir Institute of Technology, Molecular Biology and Genetics, Izmir, 2021
Text in English; Abstract: Turkish and English
Keywords: Endothelial cells; Hypoxia models; Blood brain barrier